The birdmen of the Pleistocene: On the relationship between Neanderthals and scavenging birds. (9th November 2016) - Finlayson, Stewart; Finlayson, Clive
Abstract: We have examined 192 Middle Palaeolithic sites in the Palaearctic which have raptor and corvid bones associated in human occupation contexts. We have also examined 395 sites with Upper Palaeolithic contexts for comparison. We show that Neanderthals were regularly associated with a suite of birds of prey and corvids. We identify that the main species were regular or seasonal scavengers which co-occurred across large areas of the Neanderthal geographical range. This suggests a long-standing inter-relationship between Neanderthals, raptors and corvids. We propose that the degree of difficulty of capturing these species was not an insurmountable problem for the Neanderthals and provide present-day examples of close interaction between scavenging birds and people. We also show that modern humans had a similar relationship with the same suite of birds as the Neanderthals. We suggest that one possibility is that Neanderthals transmitted the behaviour to modern humans.